2010
DOI: 10.1111/j.1600-0404.2009.01232.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of depression in multiple sclerosis patients

Abstract: Gay M‐C, Vrignaud P, Garitte C, Meunier C. Predictors of depression in multiple sclerosis patients.
Acta Neurol Scand: 2010: 121: 161–170.
© 2010 The Authors Journal compilation © 2010 Blackwell Munksgaard. Depression is one of the major problems associated with multiple sclerosis (MS). Several physical and psychological factors tend to interact and make it difficult to pinpoint the predictors of the depression. It seemed particularly important to examine how anxiety and illness evolution (characterized by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
73
0
10

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(103 citation statements)
references
References 66 publications
20
73
0
10
Order By: Relevance
“…Consistent with previous reports, HADS' depression scores among MS patients were significantly higher for women [2,6,28] and were significantly associated with higher disability, as measured by EDSS [17,28,30,31]. The study also documented a significant association with faster progression of MS, as measured by MSSS.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous reports, HADS' depression scores among MS patients were significantly higher for women [2,6,28] and were significantly associated with higher disability, as measured by EDSS [17,28,30,31]. The study also documented a significant association with faster progression of MS, as measured by MSSS.…”
Section: Discussionsupporting
confidence: 90%
“…A study of 50 MS patients attending an outpatient clinic reported that BDI scores increased with disease severity and physical disability but not with disease duration (15,(27)(28)(29)(30)(31) In this study we found a significant correlation between depression and an objective measure of disability, the EDSS. Separate calculations of the correlation between depression and the 8 functional systems of the EDSS revealed that only bowel and bladder dysfunction and sensitive score were correlated with BDI score.…”
Section: Resultssupporting
confidence: 55%
“…Twenty-three patients showed no symptoms of depression (BDI score 1-10), 4 patients had mild mood disturbance (BDI score 11-16), 3 had borderline clinical depression (BDI score [17][18][19][20], and 2 had moderate depression (BDI score [21][22][23][24][25][26][27][28][29][30]. The mean BDI score was 8.71±7.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors [60,61] were unable to find significant correlations between the EDSS score and depressive scores. Most studies, however, found that MS patients with higher EDSS scores had significantly higher depression scores, while significant positive correlations were found between the EDSS and depression scores [62][63][64][65][66][67][68]. This is important as MS functional disability and especially depression predict physical health and quality of life [69][70][71].…”
Section: Discussionmentioning
confidence: 95%